DNA Sequencing Protocols - Graham, Colin A;Ed. Hill, Alison J. M;Ed (Methods in molecular biology (Clifton, N.J.), v. 167., 2001)
A collection of powerful PCR-based methods for DNA sequencing, many suitable for human genome sequencing and mutation detection in human disease. This book offers material on automated DNA sequencers, capillary DNA sequencers, heterozygote mutation detection, web-based sequencing databases and genome sequencing sites, and the human genome project.